Kelembagaan Pendukung Pembelajaran Petani dalam Pengelolaan Hutan Rakyat Lestari (Kasus di Kab. Gunung Kidul, Provinsi Daerah Istimewa Yogyakarta dan Kabupaten Wonogiri, Provinsi Jawa Tengah) - Yumi Yumi; Sumardjo Sumardjo; Darwis S Gani; Basita Ginting Sugihen (Jurnal Penyuluhan, 2012)
Forest Management is facing the challenge of implementing the sustainable forest management which includes private forest. Successfully gained the Ecolabel Certificate, some private forest management units in Central Java and Yogyakarta’s districts prove that the small units run by farmers are able to implement the sustainable forest management. The farmers’ success in implementing the sustainable forest management must have been gained through learning process. How the learning process was and what farmers’ learning support institutions influencing of the sustainable private forest management were, were the research questions of this study. The study used explanatory survey method on 200 farmers in Gunung Kidul and Wonogiri. Data collection was conducted from December 2009 to February 2010. The data were analyzed by using descriptive technique and Structural Equations Model (SEM). The conclusions are: (1) there are significant differentiation about farmer’s learning support institutions in Gunung Kidul and Wonogiri. In Gunung Kidul District the institutions are integrated in one team work which legitimated by Bupati (the Head of District); (2) farmers’ learning intensity is low. It was significantly influenced by farmers’ learning support institutions; (3) farmers’ learning intensity can be improved by farmer empowerment activities and competent personnels.Keyword: Sustainable private forest management, farmers’ learning process, support system of farmer’s learning institutions, collaboration